Effect of hydrogen enrichment on flame broadening of turbulent premixed flames in thin reaction regime. (1st January 2021) - Zhang, Weijie; Wang, Jinhua; Lin, Wenjun; Li, Guohua; Hu, Zhiyun; Zhang, Meng; Huang, Zuohua
Abstract: An experimental study to identify the effect of hydrogen enrichment and differential diffusion on the flame broadening is conducted. Turbulent lean premixed flames in the Broadened Preheat–Thin Reaction (BP-TR) regime are obtained. The flames are stabilized on a Bunsen burner and CH4 /H2 /air mixtures are adopted with three hydrogen fractions of 0, 30% and 60%. The preheat zone and heat release zone are captured with the multi-species Planar Laser-Induced Fluorescence (PLIF) of OH and CH2 O radicals. Flame thicknesses of the preheat and heat release layers are measured. Results show broadened preheat zone and thin heat release layers for the flames, as predicted by the BP-TR regime. The preheat zone thickness can be increased to about 3–6 times compared to the laminar preheat thickness. An apparently decreased preheat zone thickness with hydrogen addition is observed. The differential diffusion is anticipated to locally thicken the heat release zone along the flame front. The mean heat release thickness is nearly not affected by the turbulence or hydrogen addition. Highlights: The detailed turbulent flame structure with hydrogen addition is studied. Broadened preheat and thin heat release layers are captured. Broadening of the preheat zone is mitigated by the hydrogen addition. The heat release zone can be locally thickened with differential diffusion.